Computational Modeling of the Subject-Specific Effects of Annuloplasty Ring Sizing on the Mitral Valve to Repair Functional Mitral Regurgitation - Gaidulis, Gediminas; Padala, Muralidhar (Annals of biomedical engineering, 2023)
Surgical repair of functional mitral regurgitation (FMR) that occurs in nearly 60% of heart failure (HF) patients is currently performed with undersizing mitral annuloplasty (UMA), which lacks short- and long-term durability. Heterogeneity in valve geometry makes tailoring this repair to each patient challenging, and predictive models that can help with planning this surgery are lacking. In this study, we present a 3D echo-derived computational model, to enable subject-specific, pre-surgical planning of the repair. Three computational models of the mitral valve were created from 3D echo data obtained in three pigs with HF and FMR. An annuloplasty ring model in seven sizes was created, each ring was deployed, and post-repair valve closure was simulated. The results indicate that large annuloplasty rings (> 32 mm) were not effective in eliminating regurgitant gaps nor in restoring leaflet coaptation or reducing leaflet stresses and chordal tension. Smaller rings (≤ 32 mm) restored better systolic valve closure in all investigated cases,but excessive valve tethering and restricted motion of the leaflets were still present. This computational study demonstrates that for effective correction of FMR, the extent of annular reduction differs between subjects, and overly reducing the annulus has deleterious effects on the valve.